Are all wetland models the same? Comparing wetland models and streamflow regulation of catchment-scale hydrological modelling tools under a changing climate - Metho, Penisoh (Department of Environmental and Geographical Science, 2023)
Comparing how wetlands are simulated in different hydrological modelling tools is needed to identify their suitability in different contexts. A simulated wetland will result in predictions of streamflow regulation, e.g., storing flood water and reducing high flows and releasing water in drier periods, which may or may not be realistic for a given area. Evaluating wetland models is critical for navigating the different types of physical wetlands with variable influences on streamflow, and the different simulated wetlands conceived in the plethora of modelling tools (i.e. software) available for use. A recent study found that sometimes wetlands are excluded from hydrological models used to inform water resource decisions. When wetlands are included in a hydrological model, few studies identify process similarities between the actual and modelled wetland or the realism of the modelled impacts of the wetland on streamflow before applying the model's output to water resource decisions. This research aims to identify and evaluate wetland characteristics, processes and impacts on catchment streamflow in different modelling tools and models (i.e. setups in a tool). Evaluating wetland models supports wetland-inclusive modelling and ensures that a wetland model is hydrologically sound and suitable. An unchannelled valley-bottom wetland located in the upper Kromme catchment, Eastern Cape, South Africa, was used. Wetland models were compared as independent units conceptually and as functional units within the catchment by modelling. First, using qualitative analysis, a conceptual assessment of wetland model structures in ACRU, WRSM-Pitman, MIKE SHE coupled with Hydro River and SWAT were considered in the context of the case study wetland. Second, using quantitative analysis, model outputs from wetland models in ACRU and WRSM-Pitman were assessed for model performance, behaviour and streamflow regulation during droughts and floods. The predicted impact of the wetland on catchment hydrology was determined from scenarios with and without a wetland and modelled wetland storage fluxes over the whole simulation period, four severe floods and three drought periods. The results from the qualitative and quantitative comparisons suggest that similarities between the physical and simulated wetland improves the likelihood of model suitability, good model performance and streamflow regulation predictions. Additionally, models setup for the same wetland with the same input data simulated potentially acceptable but different streamflow totals: for an observed total of 9.13 Mm3 ; WRSM-Pitman's comprehensive wetland simulated 10.64 Mm3 ; and from ACRU's riparian zone and wetland HRU's simulated 11.31 Mm3 and 8.89 Mm3 , respectively. Modelled actual evapotranspiration was underestimated by the riparian zone wetland (946.08 mm), overestimated in the comprehensive wetland model (2 054.80 mm) and moderately similar in the wetland HRU when compared with remotely-sensed data (1 520.30 mm). During extreme events, all models simulated flood attenuation while drought responses were variable (two wetland models predicted streamflow attenuation). By implication, the results suggest that good model performance does not guarantee the simulation of expected streamflow regulation roles recorded in literature. Furthermore, variable water yields and wetland impacts from the models demonstrated the possibility for different modelling efforts to result in different water supply, use and conservation measures. The study highlights the importance of contextualising model output for catchments with wetlands before applying the simulations to impact assessments or future climate scenarios.